2016
DOI: 10.1155/2016/8502123
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of Sulfated Polysaccharides from Mexican Seaweeds against Measles Virus

Abstract: Sulfated polysaccharides (SPs) extracted from five seaweed samples collected or cultivated in Mexico (Macrocystis pyrifera, Eisenia arborea, Pelvetia compressa, Ulva intestinalis, and Solieria filiformis) were tested in this study in order to evaluate their effect on measles virus in vitro. All polysaccharides showed antiviral activity (as measured by the reduction of syncytia formation) and low cytotoxicity (MTT assay) at inhibitory concentrations. SPs from Eisenia arborea and Solieria filiformis showed the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 59 publications
4
33
1
Order By: Relevance
“…Five species of Mexican macroalgae were used in this study, three from Baja California ( Macrocystis pyrifera , Ecklonia arborea (formerly Eisenia arborea ), and Silvetia compressa (formerly Pelvetia compressa ), one green seaweed from Southern Baja California ( Ulva intestinalis ), and one red seaweed from Yucatan ( Solieria filiformis ). In a previous study, our group reported in detail the collection of these five seaweeds [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five species of Mexican macroalgae were used in this study, three from Baja California ( Macrocystis pyrifera , Ecklonia arborea (formerly Eisenia arborea ), and Silvetia compressa (formerly Pelvetia compressa ), one green seaweed from Southern Baja California ( Ulva intestinalis ), and one red seaweed from Yucatan ( Solieria filiformis ). In a previous study, our group reported in detail the collection of these five seaweeds [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, we tested the antiviral activity in vitro against MeV of Polyphenol-rich extracts isolated from five Mexican seaweeds. We tested the combined antiviral effect of the best polyphenols with ribavirin and with sulphated polysaccharides isolated from the same seaweeds with potent antiviral properties [ 13 ]. The main goal of this research was to discover new candidates of antiviral drugs with a low cytotoxicity and affordable cost of production that could help control viral infection diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Polyphenolic compounds have demonstrated antiviral activity against HIV [ 58 ], Herpes Virus (HV) [ 59 , 60 ], and Measles Virus (MV) [ 61 ]. Among them, phlorotannins biosynthesized via the acetate malonate pathway [ 62 ] comprise a whole spectrum of molecules produced by brown seaweed [ 63 ] with anti-allergic [ 64 ], antioxidant [ 65 ], and photoprotective [ 66 ] properties; with noticeable bioactivity in virus-related studies that include the Influenza virus [ 67 , 68 ], HIV [ 69 ], and Hepatitis Virus [ 70 ].…”
Section: Algae-derived Antiviral Compoundsmentioning
confidence: 99%
“…The ulvan SU1F1 from E. compressa inhibited viral penetration and had virucidal effects on HSV-1 [ 147 ]. SPs from U. intestinalis had low antiviral activity on the measles virus compared to SPs isolated from the seaweeds Eisenia arborea and Solieria filiformis [ 61 ]. The SPs from U. pertusa significantly induced avian influenza virus specific antibodies in vivo [ 148 ].…”
Section: Algae-derived Antiviral Compoundsmentioning
confidence: 99%
“…Quantitative Real-Time PCR was performed, total RNA was isolated from treated Vero cells using TRIzol™ Reagent Invitrogen™ (Thermo Fisher Scientific, Bedford, MA, USA). Reverse transcription was carried out using the High Capacity cDNA Reverse Transcription Kit (Applied Biosystems, Beverly, MA, USA) and the viral genome was amplified with the specific primers: MeVF: 5 GAGGGTCAAACAGAGTCGAG 3 , MeVR: 5 CGGTTGGAAGATGGGCAG 3 that amplified a 95 nt fragment [11]. The real-time PCR was carried out using PowerUp™ SYBR™ Green Master Mix (Applied Biosystems, Beverly, MA, USA) and the Applied Biosystems StepOne Real Time PCR System following procedures: 95 • C for 2 min, followed by 40 cycles of 95 • C for 2 s, 60 • C for 10 s, and 72 • C for 20 s. The number of viral copies was calculated by using a standard curve.…”
Section: Rt-qpcrmentioning
confidence: 99%